Efektifitas Media Booklet Terhadap Pengetahuan Remaja Tentang Bahaya Merokok di SMA Santo Lukas Jakarta Utara: Ami Kadewi, Emilia, Surandi Ketaren - Ami Kadewi; Emilia Emilia; Surandi Ketaren (STIKes Persada Husada Indonesia, 2025)
Adolescence often occurs in various environments, including school, peers, and family. The influence of peers and the school environment can make someone more vulnerable to trying smoking. If friends or role models in the family smoke, adolescents may feel more inclined to try smoking. The purpose of this article is to analyze the relationship between education using booklets and adolescents' knowledge about the health dangers of smoking at Santo Lukas High School, North Jakarta. This study used a quantitative design, conducted at a school in North Jakarta. The inclusion criteria were respondents aged 15-16 years and exclusion criteria were respondents who withdrew during the event. Demographic data used in this study included age and gender. The results obtained before the education using booklets, the majority were in the moderate category with a total of 18 students (75%), then after the education, there was an increase of 21 students (87.5%) in the highest category, with a p-value of 0.001 and a difference of 0.63. Providing health education using booklets has an effect on knowledge about the dangers of smoking.